TECNOESTRESSE E SUAS RELAÇÕES COM RESILIENCIA, MOTIVAÇÃO E PRODUTIVIDADE DA TECNOLOGIA DA INFORMAÇÃO - Loyola, Luiz Carlos Mota (2016)
The major concern of organizations today is to improve the productivity of their employees and the use of information technology has a notorious role for this goal to be achieved. Excessive use of information technologies can make the employee feel stressed and thus compromise their results and consequently the objectives of the organization. Stress resulting from the excessive use of technology is known as technosurgery, which can significantly affect several factors of the organization, among them the perceived productivity of the technologies by the collaborators. Some aspects can be considered as inhibitors of the tecnoestresse, as, for example, the resilience, extrinsic motivation and dependence of the technology for the accomplishment of the tasks. This study examined how these characteristics influence the stress of information overload and the invasion of privacy over the perceived productivity of information technology. Through a quantitative approach, the data were collected through a research instrument with the answers of 354 questionnaires. It is concluded that individual resilience negatively influences technoinvasion, which, in turn, negatively influences IT productivity and that IT dependence to perform tasks positively influences techno-load such as technoinvasion.